Developing Egyptian water quality index for drainage water reuse in agriculture. (7th February 2019) - El‐Sayed, A.; Shaban, M.
Abstract: In Egypt, water quality (WQ) is an ordinary activity. However, the calculation of a tailor‐made Egyptian WQ index is not. Therefore, this research attempts to develop an index for the agricultural drainage water (EG‐DWQI) that can be reused for irrigation based on collected WQ data measured monthly from August 2000 to July 2015. The development of the EG‐DWQI was carried out in four main steps, namely, parameters selection, parameter transformation to a common scale, assignment of parameters weights, and aggregation of subindices to produce a final index score. In its final form, the index can be easily estimated using a set of rating curves and their corresponding equations that were statistically tested and proved to be verified. The developed index was successfully employed to delineate the drainage WQ status that can be reused for irrigation in the Nile Delta of Egypt as benchmarking for future comparisons. The EG‐DWQI is proved to be easy, fast, and does not entail complex mathematics and can be easily managed by means of a spreadsheet. Practitioner points: This research develops a tailor made water quality index for assessing agricultural drainage water that can be re‐used for irrigation. Then, the developed index was successfully employed to delineate the water quality in the main drains located in the Nile Delta of Egypt as benchmarking for future comparisons. The application of the index is proved to be easy, fast and does not entail complicated mathematics especially with the new computer facilities.